Cyclopenta[hi]aceanthrylene Decorated with Multiple and Long Alkoxy Chains: Physicochemical Properties and Single-Walled Carbon Nanotubes' Exfoliation Capability. (22nd June 2020) - Schierl, Christoph; Pardo, Virtudes; Bottari, Giovanni; Guldi, Dirk M.; Torres, Tomas
Abstract : A rod-like cyclopenta[ hi ]aceanthrylene (CPA) derivative bearing three dodecyloxy chains at each of its two terminal positions was prepared. Spectroscopic (i.e., steady-state absorption and fluorescence) and electrochemical studies carried out with this polycyclic aromatic hydrocarbon (PAH) derivative showed an intense absorption through the entire UV–vis spectral range, weak fluorescence, small HOMO-LUMO gap, and excellent electron accepting capability. Transient absorption spectroscopy (TAS) revealed the formation of singlet and triplet excited states; the latter was, however, only observed in the presence of a triplet sensitizer. The exfoliation capability of this lipophilic CPA towards single-walled carbon nanotubes (SWCNTs) in THF was also investigated. On one hand, transmission electron microscopy (TEM) pointed to an efficient debundling of SWCNTs by the CPA derivative by means of non-covalent interactions. On the other hand, important differences in the ground and excited state features of the uncomplexed and SWCNT-complexed CPA were revealed by Raman and TAS.